Analisis Optimalisasi Sistem Penempatan Pegawai Negeri Sipil Berbasis Kompetensi pada Balai Pemasyarakatan Kelas II Bukittinggi - Hadi Susilo; Yulihasri Yulihasri; Zuripal Zuripal (Pusat Riset dan Inovasi Nasional, 2022)
In this thesis the author discusses the Optimization Analysis of Competency-Based Civil Servant Placement System at the Class II Bukittinggi Penitentiary. This study aims to determine what factors are obstacles to the Optimization of Competency-Based Civil Service Placement System at the Class II Bukittinggi Correctional Center. The data collection technique used by the author is library research and field studies by conducting direct interviews with related parties. The results of this study indicate that the optimization of competency-based civil servant placement is very important in carrying out the duties and functions of the employees themselves and to achieve organizational goals. There are several obstacles in optimizing the placement of competency-based employees such as the formation of the Ministry of Law and Human Rights of the Republic of Indonesia that is not appropriate, competencies that are not in accordance with the needs in the field. The lack of education and training for the Bukittinggi Class II Fathers Board employees.